Development of protein enriched shrimp croquette from shrimp industry wastes - Khan, M; Rahman, ML; Rahman, ML; Alam, AKM Nowsad (Journal of the Bangladesh Agricultural University, 2014)
Protein fortified and tasty shrimp croquette was developed from different component parts of shrimp wastes by using a combination of vegetables (potato, Colocasia, green banana, green papaya and spinach), spices (green chili, onion, garlic, turmeric, red pepper and ginger) and other ingredients (salt, wheat flour, egg, sugar and milk powder). The ingredients were mixed with variable quantities of shrimp shell powder (3, 5 and 10%), shaped and covered with egg and bread crumb. Proximate composition of shrimp shell powder (SSP) and shrimp croquette was determined as crude protein, crude lipid, ash and moisture. It was observed that the SSP contained 47.48±0.74% crude protein indicating its potentiality as a good protein source for the food industry. The lipid content of SSP was 10.50±0.71% and 19.61±0.64%. When SSP was used in the croquette, protein content increased with the higher levels of SSP. The final protein content found were 7.22±0.66, 9.39±0.37 and 11.73±0.61% in the croquettes added with 3, 5 and 10% SSP, respectively. The suggested recipes containing 5% SSP were preferred by the panelists on the basis of their overall quality. Sensory, chemical and microbiological quality changes of shrimp croquette were determined to evaluate the shelf life and storage stability under different storage conditions. At room temperature shelf life of shrimp croquette was very short, in fact not more than 24 hours. On the other hand, at refrigeration temperature it remained in good condition up to 10 days. At frozen storage it remained in good condition for 1 month. The research reveals that good quality protein fortified shrimp croquette could be manufactured from shrimp shell wastes. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19937 J. Bangladesh Agril. Univ. 11(2): 331-340, 2013